Аналіз розвитку виробництва продукції з комплексним використанням сировини - Тимофєєв, Володимир Миколайович; Жадан, Тетяна Андріївна (НТУ "ХПІ", 2006)
Tendencies of development of production with complex use of raw material and presence of a seasonal wave are established. It is recommended results of the analysis to use in forecasting.
Keywords: прогнозування; хвиля сезонна; методи статистичні; ряди динамічні; олія соняшникова; продукція маргаринова; майонез; обсяг виробництва